Ksiądz Pułkownik Józef Panaś (1887–1940) Kapelan Legionów Polskich, działacz polityczny i publicysta - Stawarz, Przemysław (Zeszyty Wiejskie, 2017)
The purpose of this dissertation is to present the significant achievements and activities of this chaplain in many areas of his life. He is not a person well known and has not gained a rightful place in the Polish historiography. The author of this dissertation attempted to analyze the role of chaplain in the functioning of the Polish Legions, the battle for Przemyśl and pastoral work in the Polish Army. Also considered the impact of the priest chaplain on the activities of the peasant movement, attempted to determine the degree of the impact of journalism Socio-political face of ideological and programmatic opposition government. The author did not omit the question of the position of chaplain in the structures of conspiracy Lvov under Soviet occupation.